THE ROLE OF AI-POWERED TOOLS IN ENHANCING VOCABULARY ACQUISITION AMONG BEGINNER LEARNERS - Tomokazu, Ono (The Lingua Spectrum, 2025)
This study explores the impact of AI-powered tools on vocabulary acquisition among beginner learners. The research investigates how artificial intelligence applications, such as language learning apps and chatbots, facilitate the retention and recall of new words. Using a mixed-method approach, data were collected from 50 beginner learners through pre- and post-tests and interviews. The results indicate that AI tools significantly enhance vocabulary retention, increase learner motivation, and provide personalized learning experiences. The study concludes that integrating AI-powered tools in language education offers substantial benefits for beginner learners and recommends further research on their long-term effectiveness.